2021
DOI: 10.1007/s12237-021-00899-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Resiliency of Salt Marshes Under Increasing Nitrogen Loading

Abstract: Understanding the threat to ecosystems from excess nitrogen in coastal waters is a priority issue in scientific research and natural resource management. Previous field studies have demonstrated that high nitrogen loading can decrease the health and resiliency of salt marshes through shifting biomass allocation, increasing decomposition, and causing creek bank instability, all of which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 52 publications
1
9
1
Order By: Relevance
“…35 Experimental additions of N to S. patens and S. alterniflora patches displayed a reduction in below-ground root biomass, but an increase in above-ground biomass, suggesting that nutrient foraging was eased. 9,36,37 In addition to shifts in biomass production, other studies found that N addition caused spore biovolume and density of extraradical hyphae to decrease. 10,33,38 These observations are consistent with the resource-ratio hypothesis, which states that more competitive and successful species will grow in habitats with lower resource levels.…”
Section: Effects Of Eutrophicationmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Experimental additions of N to S. patens and S. alterniflora patches displayed a reduction in below-ground root biomass, but an increase in above-ground biomass, suggesting that nutrient foraging was eased. 9,36,37 In addition to shifts in biomass production, other studies found that N addition caused spore biovolume and density of extraradical hyphae to decrease. 10,33,38 These observations are consistent with the resource-ratio hypothesis, which states that more competitive and successful species will grow in habitats with lower resource levels.…”
Section: Effects Of Eutrophicationmentioning
confidence: 99%
“…9,36 As N is added to soils, there is a subsequent release of CO₂, indicating there is an increase in microbial respiration. 37 This is likely due to a reduction in bacterial-fungal competition. As AMF biomass diminishes with increasing N addition, competition for N between fungi and saprotrophic bacteria is eased, leading to an increase in bacterial populations and decompositional activities.…”
Section: Effects Of Eutrophicationmentioning
confidence: 99%
“…Previous studies have described both positive and negative impacts of enhanced nutrient availability on coastal wetland stability [8][9][10][11]. This uncertainty is problematic for land managers faced with coastal wetland drowning [12][13][14][15][16] due to uncertainty regarding the potential role anthropogenic nutrient enrichment may play in this loss [17]. As coastal marshes are known to be nutrient limited, fertilization has been found to enhance growth, productivity [11] and shoot density [18], which boosts sediment trapping and accretion via enhanced baffling [19].…”
Section: Introductionmentioning
confidence: 99%
“…Here we focus on assessing a novel suite of metrics to reveal whether two eutrophic estuaries in California and New York that are undergoing rapid marsh loss [12,24] are experiencing the negative effects of eutrophication. By focusing on marshes in California and New York, we overcome issues with nutrient gradients that coincide with other gradients (such as that in salinity and tidal range) [17,45] and sample marshes with different ecosystem dominant species (Spartina alterniflora in New York and Salicornia pacifica in California). At Jamaica Bay, which is located in New York City between Brooklyn and Queens, decades to centuries of treated and untreated sewage discharges have interacted with other anthropogenic stressors (e.g., dredging; filling in; land development) causing alteration of the salt marsh system geomorphology and habitat integrity.…”
Section: Introductionmentioning
confidence: 99%
“…The structural and functional characteristics of tidal marshes are considered in several studies (James et al 2020;Jones et al 2020;Curran et al 2021;Kimball and Eash-Loucks 2021;Smith and Pellew 2021), supported with examples that apply contemporary approaches for exploring these characteristics (Bennett et al 2020;Baker et al 2021;Colombano et al 2021a;zu Ermgassen et al 2021a). System change within tidal marshes is considered in the context of factors that impact their health, resilience and productivity (Crosby et al 2021), and the implications for marsh nekton (Harris et al 2020). The special issue concludes with some contemporary analyses of restoration endeavours and the economic outcomes that may be derived from repair and factors that contribute to success (Armitage 2021;Weinstein et al 2021).…”
mentioning
confidence: 99%